The Culture of Community Life in the Context of National Identity - Demirtshyan, Movses (Bulletin of Yerevan University E: Philosophy, Psychology, 2022)
Modern processes of globalization present new challenges for different societies and cultures, as they relate to everyday relationships of people and change the way of life that has developed over the centuries. When living conditions change very slowly - over the course of dozens of generations, the reproduction of culture, which acts primarily as a system of prohibitions, is able to organize the life of each subsequent generation in the same way through norms, values and ideals inherited from the past, which may not change significantly, because the social environment hasn`t changed. But in the modern world, when radical changes take place already in the life of one generation, it is obvious that simple reproduction can no longer give the culture viability and duration. The article shows that rich and viable, first of all, is the culture that is able to adapt to the changing reality and offer alternative ways of organizing life. Alternative in this case are all mechanisms that allow groups of people (nations, ethnic groups), while maintaining their cultural identity, to express themselves and find their place in a changing reality. This experience of adaptation and survival was also historically acquired by the Armenian people, who, in the conditions of geographical fragmentation and deprived of the opportunity to unite into a single national state, were forced to organize their lives through autonomous cultural communities. The main task of cultural communities was mainly survival, not development, but thanks to this, members of the communities acquired such qualities as initiative, flexibility, awareness of belonging to “we” (family, community). This rich experience of Armenian culture is also the basis for the fact that in this case the culture takes birth to a nation-state, unlike many Western countries, where the nation-state purposefully creates and disseminates national culture - a common language, norms of behavior, narratives, values, etc.